Attenuation of TeV γ-rays by the starlight photon field of the host galaxy - Zacharias, Michael; Chen, Xuhui; Wagner, Stefan (Arxiv, 2016)
The absorption of TeV $γ$-ray photons produced in relativistic jets by surrounding soft photon fields is a long-standing problem of jet physics. In some cases the most likely emission site close to the central black hole is ruled out because of the high opacity caused by strong optical and infrared photon sources, such as the broad line region. Mostly neglected for jet modeling is the absorption of $γ$-rays in the starlight photon field of the host galaxy. Analyzing the absorption for arbitrary locations and observation angles of the $γ$-ray emission site within the host galaxy we find that the distance to the galaxy center, the observation angle, and the distribution of starlight in the galaxy are crucial for the amount of absorption. We derive the absorption value for a sample of $20$ TeV detected blazars with a redshift $z_r<0.2$. The absorption value of the $γ$-ray emission located in the galaxy center may be as high as $20%$ with an average value of $6%$. This is important in order to determine the intrinsic blazar parameters. We see no significant trends in our sample between the degree of absorption and host properties, such as starlight emissivity, galactic size, half-light radius, and redshift. While the uncertainty of the spectral properties of the extragalactic background light exceeds the effect of absorption by stellar light from the host galaxy in distant objects, the latter is a dominant effect in nearby sources. It may also be revealed in a differential comparison of sources with similar redshifts.